Effect of Cement Replacement with Carbide Waste on the Strength of Stabilized Clay Subgrade - Agus Setyo Muntohar; Edi Hartono; Wilis Diana; Anita Rahmawati (Civil Engineering Dimension, 2016)
Cement is commonly used for soil stabilization and many other ground improvement techniques. Cement is believed to be very good to improve the compressive and split-tensile strength of clay subgrades. In some application cement could be partly or fully replaced with carbide waste. This research is to study the effectiveness of the cement replacement and to find the maximum carbide waste content to be allowed for a clay subgrade. The quantities of cement replaced with the carbide waste were 30, 50, 70, 90, and 100% by its mass. The results show that replacing the cement with carbide waste decreased both the compressive and split tensile strength. Replacing cement content with carbide waste reduced its ability for stabilization. The carbide waste content should be less than 70% of the cement to provide a sufficient stabilizing effect on a clay subgrade.